Urbanization and small household agricultural land use choices in the Brazilian Amazon and the role for the water chemistry of small streams. Issue 2 (3rd March 2016) - Cak, Anthony D.; Moran, Emilio F.; Figueiredo, Ricardo de O.; Lu, Dengsheng; Li, Guiying; Hetrick, Scott
Abstract : Many small watersheds and streams in the Brazilian Amazon have been impacted by agriculture and urban development, often due to household economic needs and migration processes. This study examined the relationships between land use, soil type, and household factors on stream water chemistry in and near the city of Altamira, Pará, Brazil, in 2008–2009. While soil weathering and stream discharge may have affected several stream water ion concentrations, agriculture and especially urban development were associated with high dissolved nitrogen concentrations, high water temperatures, and low dissolved oxygen concentrations in streams. Younger interviewed households were generally associated with these watersheds, and many urban residents reported disposing of household waste directly into streams. In contrast, older households were generally associated with forest and cocoa agriculture, along with lower water temperatures and higher dissolved oxygen concentrations in streams. These conditions persisted despite reported uses of herbicides and fertilizers by some residents.